2024
DOI: 10.1088/1475-7516/2024/04/061
|View full text |Cite
|
Sign up to set email alerts
|

Black hole solutions with constant Ricci scalar in a model of Finsler gravity

Z. Nekouee,
S.K. Narasimhamurthy,
S.K.J. Pacif

Abstract: Ricci scalar being zero is equivalent to the vacuum field equation in Finsler space-time. The Schwarzschild metric can be concluded from the field equation's solution if the space-time conserves spherical symmetry. This research aims to investigate Finslerian Schwarzschild-de Sitter space-time. Recent studies based on Finslerian space-time geometric models are becoming more prevalent because the local anisotropic structure of space-time influences the gravitational field and gives rise to modified co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…. This example has been used to find black hole solutions with constant Ricci scalar in a model of Finsler gravity in dimension two [23].…”
Section: Remark 33 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…. This example has been used to find black hole solutions with constant Ricci scalar in a model of Finsler gravity in dimension two [23].…”
Section: Remark 33 (A)mentioning
confidence: 99%
“…Conic pseudo-Finsler surfaces are used widely in applications, especially in physics. For example, in [23], Nekouee et al showed that the Finslerian sphere plays a crucial role in the classical Schwarzschild-de Sitter metric perturbation. In other words, they found a Finslerian Schwarzschild-de Sitter solution with the symmetry of Finslerian sphere from the Finsler structure of Randers type.…”
Section: Introductionmentioning
confidence: 99%